Particle transport within the pulsar wind nebula HESS J1825-137 - Abdalla, Hassan; Glawion, Dorit; Jankowsky, Felix; Mohamed, Mahmoud; Quirrenbach, Andreas; Schwemmer, Stephanie; Wagner, Stefan (Astronomy and astrophysics, 2019)
We present a detailed view of the pulsar wind nebula (PWN) HESS J1825-137. We aim to constrain the mechanisms dominating the particle transport within the nebula, accounting for its anomalously large size and spectral characteristics.Aims. The nebula was studied using a deep exposure from over 12 years of H.E.S.S. I operation, together with data from H.E.S.S. II that improve the low-energy sensitivity. Enhanced energy-dependent morphological and spatially resolved spectral analyses probe the very high energy (VHE, E > 0.1 TeV) γ-ray properties of the nebula.Methods. The nebula emission is revealed to extend out to 1.5° from the pulsar, ~1.5 times farther than previously seen, making HESS J1825-137, with an intrinsic diameter of ~100 pc, potentially the largest γ-ray PWN currently known. Characterising the strongly energy-dependent morphology of the nebula enables us to constrain the particle transport mechanisms. A dependence of the nebula extent with energy of R ∝ Eα with α = −0.29 ± 0.04stat ± 0.05sys disfavours a pure diffusion scenario for particle transport within the nebula. The total γ-ray flux of the nebula above 1 TeV is found to be (1.12 ± 0.03stat ± 0.25sys) × 10−11 cm−2 s−1, corresponding to ~64% of the flux of the Crab nebula.Results. HESS J1825-137 is a PWN with clearly energy-dependent morphology at VHE γ-ray energies. This source is used as a laboratory to investigate particle transport within intermediate-age PWNe. Based on deep observations of this highly spatially extended PWN, we produce a spectral map of the region that provides insights into the spectral variation within the nebula.
Gesehen am 19.08.2020